UNDERSTANDING SOCIAL JUSTICE AND RESERVATION POLITICS: IMPLICATIONS FOR DEMOCRATIC PARTICIPATION IN TUMKUR DISTRICT - H, Rangaswamaiah; K.C, Suresha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the intersection of reservation policies, social justice, and political participation. Using a sample of 50 respondents from diverse demographic backgrounds, the research examines awareness, perceptions, and the socio-political impact of reservation policies within the district. The findings reveal that 50% of respondents are fully aware of reservation policies, while 30% are partially aware. However, perceptions of fairness are divided—40% believe the policies are fair, while 30% view them as unfair. Regarding employment opportunities, 36% of participants reported positive outcomes from reservation policies, though 24% highlighted negative impacts. Caste-based electoral participation indicates that OBCs and SC/ST groups show higher engagement, with over 80% regularly participating in elections. Trust in political leaders advocating for reservation policies remains moderate, with 50% expressing moderate trust. Furthermore, the study finds that reservation politics significantly influences voting behavior in 40% of respondents. While 50% report satisfaction with government policies promoting social justice, others raise concerns about persistent discrimination, bureaucratic barriers, and lack of awareness affecting social inclusion. The data also suggest that access to government welfare schemes varies by caste, with OBC and SC/ST groups reporting higher participation rates. These findings emphasize the complexities of reservation politics and its dual role in promoting both inclusion and division. Overall, the study highlights the critical need for equitable policy implementation to foster democratic participation and enhance social justice in Tumkur District.